2002
DOI: 10.2460/ajvr.2002.63.1048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of background serum lithium concentrations on the accuracy of lithium dilution cardiac output determination in dogs

Abstract: The LiDCO measurement increased slightly as the serum lithium concentration increased. This error was not clinically relevant and was minimal at a serum lithium concentration of 0.1 mmol/L and modest at a concentration of 0.4 mmol/L. The serum lithium concentration can be reliably predicted from the cumulative lithium dosage if lithium chloride is administered often within a short period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 8 publications
0
32
1
Order By: Relevance
“…In addition, only one lithium dilution was performed to determine CO at each time point to limit the effects of background lithium accumulation. Previous work has demonstrated that as many as 16 doses of lithium can be administered during several hours with minimal impact on CO (16). However, the subjects in our study experienced states of severely decreased CO, and lithium accumulation may have occurred.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In addition, only one lithium dilution was performed to determine CO at each time point to limit the effects of background lithium accumulation. Previous work has demonstrated that as many as 16 doses of lithium can be administered during several hours with minimal impact on CO (16). However, the subjects in our study experienced states of severely decreased CO, and lithium accumulation may have occurred.…”
Section: Discussioncontrasting
confidence: 59%
“…Given the dynamic and rapidly changing nature of CO in severely ill or hemorrhaged patients, frequent determinations of CO may be required. Multiple injections of indicators that are not rapidly cleared from the circulation (indocyanine green, lithium) increase the potential for background interference and tend to overestimate CO (16). Furthermore, frequent dosing with lithium chloride could result in toxicity.…”
mentioning
confidence: 93%
“…Therefore, determination of CO by this method is safe because the lithium‐selective electrode is activated by doses much lower than any pharmacological or toxic dose . In the present study, we calibrated the LiDCO plus 18 times in each dog, which could increase the risk for toxicity or even interfere with the accuracy of the monitor, as a progressive increase in the blood lithium concentration increases the overestimation of CO by LiDCO . However, we observed no sign of toxicity in our animals after recovery from anesthesia.…”
Section: Discussionmentioning
confidence: 71%
“…Blood loss associated with arterial blood withdrawal for _ Qt determination was minimal and estimated at <5% total blood volume. Likewise, the total mean cumulative dose of lithium administered was low (0.029 ± 0.005 mmol kg )1 ), and should not have affected our results (Corley et al 2002;Mason et al 2002).…”
Section: Discussionmentioning
confidence: 78%